Peningkatan Literasi Teknologi PLTS Bagi Siswa SMK Jombang-Mojokerto Melalui Pembelajaran Berbasis Industri - Imron Afandi; Ermanu AH; Moh Yogsi Wahyu; Wijaya (Sarau Institute, 2026)
The national energy transition toward renewable sources demands competent human resources, particularly at the vocational education level. This community service program aimed to enhance the photovoltaic solar panel system (PLTS) technology literacy among students in the Electrical Engineering Department of Vocational High Schools (SMK) in Jombang and Mojokerto Regencies. The program was implemented in two phases: (1) a classroom-based technical seminar covering the photovoltaic effect, key system components, MPPT and LiFePO4 technologies, DC current safety protocols, and power calculation methods; and (2) a field visit to the rooftop PLTS installation at PT Lautan Natural Krimerindo. Program effectiveness was measured using pre-test and post-test instruments via an AI-based digital quiz. Results demonstrated an average competency score increase from 63.5 to 93.7, with a combined Normalized Gain (N-Gain) of 0.82 (high category). SMKN 3 Jombang achieved a perfect N-Gain of 1.00, while SMKN 1 Pungging obtained an N-Gain of 0.52 (moderate). These findings indicate that an industry-based learning approach combining technical seminars with field observation significantly improves vocational students' technical competency. The program recommends strengthening industry-school partnerships as an effective and sustainable model for renewable energy technology knowledge transfer.